Legal concerns regarding the protection of minors’ personal data in compliance with national legislation and GDPR requirements - Yavor, Olha; Piddubna, Viktoriia; Ruban, Olena (ScienceRise: Juridical Science, 2023)
The article highlights the legal concerns surrounding the protection of minors’ personal data. The writers have conducted an original study of the sources regulating civil and labor relations in the field of acquiring and using personal data. The expansion and use of information technology and online communications can potentially lead to the violation of personal rights by the owners of personal data, both in workplace settings and in the daily lives of ordinary residents. The purpose of this article is to highlight issues concerning the collection, storage, use, and dissemination of the personal data of a minor, as well as to develop methods to protect the personal data of a child based on a comprehensive analysis of international acts, Ukrainian legislation, unique literature, and case law materials pertaining to the protection of personal data of a minor. Based on the analysis of national legislation and case law of the European Union, the author concludes that the right to personal data protection is one of the forms of realization of the right to respect for private and family life. The obligation to protect person’s rights to processing and storage of his or her private information is a negative obligation on the part of both the State and the owners of personal data. The article addresses current difficulties concerning the security of children’ personal data under current civil and medical legislation in Ukraine and other countries. The provisions of the General Data Protection Regulation, the California Consumer Privacy Act, and Ukraine’s "On Personal Data Protection" Law are compared. Possible steps to establish further protection of children’s personal data during collection and processing, whether utilizing websites, video games, online purchases, and so on, are proposed. The paper concludes that state functions should be executed without necessitating individuals’ consent for the collection of personal data. Personal data processing should be carried out within the framework and on the basis of Ukrainian laws and regulations, taking into account international conventions in this area. The analysis of methods for safeguarding children’s personal data enabled the identification of supplementary avenues for data protection. These include acquiring copies of personal data by both children and their parents, rectifying inaccuracies, completing incomplete data, exercising the ’right to be forgotten’ and the ’right to erasure’ of personal data, invalidating transactions, and seeking compensation for material and moral damages arising from the unlawful use of personal data